Jika \( |\vec{a}| = \sqrt{29} \) dan \( \left( \vec{a}+\vec{b} \right) \left( \vec{a}-\vec{b} \right) = -1 \), maka panjang vektor \( \vec{b} = \cdots \)
- \( \sqrt{21} \)
- \( 2 \sqrt{6} \)
- \( 2 \sqrt{7} \)
- \( \sqrt{30} \)
- \( 6 \)
Pembahasan:
Dari soal diketahui bahwa \( \left( \vec{a}+\vec{b} \right) \left( \vec{a}-\vec{b} \right) = -1 \), sehingga kita peroleh berikut:
\begin{aligned} \left( \vec{a}+\vec{b} \right) \left( \vec{a}-\vec{b} \right) &= -1 \\[8pt] \vec{a} \cdot \vec{a}-\vec{a} \cdot \vec{a} + \vec{b} \cdot \vec{a} - \vec{b} \cdot \vec{b} &= -1 \\[8pt] |\vec{a}|^2-|\vec{b}|^2 &= -1 \\[8pt] (\sqrt{29})^2-|\vec{b}|^2 &= -1 \\[8pt] 29-|\vec{b}|^2 &= -1 \\[8pt] |\vec{b}|^2 &= 30 \\[8pt] |\vec{b}| &= \sqrt{30} \end{aligned}
Jawaban D.